Reimagined Confucianism and the “New Woman”: Shen Yiyun and the synthesis of humanism and patriotism in modern Chinese Women’s education - Shuhui Yin (Humanities & Social Sciences Communications)
Abstract This study examines the reimagination of Confucianism in early 20th-century Chinese women’s education by the revolutionary and educator Shen Yiyun (1894–1971). Through close readings of two major texts, Guoxue Rumen Jianggao (Lecture Notes of the Introduction of Chinese Studies) and Yiyun Huiyi (Memoirs of Yiyun), supported by historical contextualization and theoretical triangulation, this paper reveals how Shen synthesized Confucian self-cultivation with modern humanist ideals to empower women as both patriotic citizens and autonomous moral agents amidst modern China’s sociopolitical crises. Tensions persisted, however, between Shen’s nationalist imperatives and her feminist aspirations, despite the fact that her educational philosophy transcended Confucian gender constraints. Underlying these tensions, it will be argued, were unresolved paradoxes in modern Confucian gender discourse.